Can the Leniency Program in Editing Cartel be Implemented in Indonesia? - Eltisha Graciana Manihuruk (Musamus Law Review, 2023)
This research is conducted to compare literature regarding the regulation and implementation of leniency programs specifically against cartels in Indonesia. The Competition Law of Indonesia under Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition does not regulate leniency programs. The United States, the European Union, Japan, South Korea, and Singapore have implemented leniency programs to combat cartels in their countries, and these have proven effective. These countries have made amendments to their anti-monopoly or anti-cartel regulations. Reflecting on these advanced nations, which have successfully implemented leniency programs, Indonesia could adopt such measures effectively. However, due to the absence of legislative regulations serving as a legal basis for leniency programs, implementation becomes challenging. Indonesia must be ready to accept and initiate a movement that can bring about changes to improve the legal system. Leniency programs to eradicate cartels are one of the ways forward for Indonesia, representing a positive new initiative.